Identification of Information Variable toward Sound Decision Making among local Government Councillors - Mohd Zool Hilmie Mohammed Sawal; Kamarudin Ngah; Zaherawati Zakaria (International Journal of Supply Chain Management, 2017)
Sound decision making is crucial in both public and private sectors because good decision able to solve problem and satisfy parties involved. As part of the government service provider, local government also expected to exercise sound decision making in their services to their community. Thus the information system plays a major role in providing good data to the decision maker. Information system helps to furnish local government officer and its community with proper information. Accurate information most needed when conditions become more uncertainty. This paper proposed a conceptual framework for information and system acceptance base on Delone and McLean information success model. Two variables are proposed to be studied; information quality and system quality. These variables are needed by decision maker at local government to come out with sound decision making since the acceptance of information is very low. The objective of this study is to come out with some solution to IT lag time which refer to large gap between the adoption of new technologies such as information integration and information sharing and their acceptance and reutilization in organization.